Gus's garage - Timmers, Leo (Gecko Press, 2017)
Gus's workshop is chockful of useless odds and ends. But when his friend Rico comes over with a problem his scooter seat is way too small for a rhino Gus finds just the thing to solve it. He creates a fabulous new vehicular contraption with an old lounge chair! One by one Gus's friends bring him their vehicles and Gus solves their troubles with ingenious solutions a cooling system made with a fridge that doubles as ice-cream machine, a burst of speed from a rocket blaster. Soon the workshop is almost empty, but the last scraps might be just enough to solve Gus's own problem at the end of a long day.